2022
DOI: 10.1002/ejic.202200010
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Emissive Lanthanide Complexes from Enantiopure [6]Helicene‐bis(pyrazolyl)‐pyridine Ligands

Abstract: Enantiopure helicene‐based bis(pyrazol‐1‐yl)pyridine (bpp‐[6]helicene), with the helicene unit in position 4 of the pyridine ring, have been prepared and structurally characterized. Their chiroptical properties have been studied experimentally, and both absorption and circular dichroism (CD) spectra have been reproduced theoretically by time‐dependent density functional theory (TDDFT). Remarkably, in spite of the remote localization of the helicene with respect to the coordination pocket of the bpp motif, chir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 90 publications
0
13
0
Order By: Relevance
“…However, generating helicene‐based metal‐organic 1D polymeric architectures remains challenging and very few examples are described in the literature [35] . Recently, we have shown that 3‐(2‐pyridyl)‐4‐aza[6]‐helicene (H6bpy) bearing a 2,2′‐bipyridine coordinating unit can accommodate a lanthanide ion and combine the inherent properties of the helicenic ligand with those of the lanthanide to create unprecedented chiral SMMs ( 1 ) (Figure 1a), [36–39] efficient singlet oxygen sensitizers, [40] and strong MChD response in the NIR range of the electromagnetic spectrum [41–43] . Despite their pertinent chiroptical properties, chiral emissive Yb III complexes are still scarce [18, 19, 44–49] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, generating helicene‐based metal‐organic 1D polymeric architectures remains challenging and very few examples are described in the literature [35] . Recently, we have shown that 3‐(2‐pyridyl)‐4‐aza[6]‐helicene (H6bpy) bearing a 2,2′‐bipyridine coordinating unit can accommodate a lanthanide ion and combine the inherent properties of the helicenic ligand with those of the lanthanide to create unprecedented chiral SMMs ( 1 ) (Figure 1a), [36–39] efficient singlet oxygen sensitizers, [40] and strong MChD response in the NIR range of the electromagnetic spectrum [41–43] . Despite their pertinent chiroptical properties, chiral emissive Yb III complexes are still scarce [18, 19, 44–49] .…”
Section: Introductionmentioning
confidence: 99%
“…[35] Recently, we have shown that 3-(2-pyridyl)-4-aza [6]-helicene (H6bpy) bearing a 2,2'-bipyridine coordinating unit can accommodate a lanthanide ion and combine the inherent properties of the helicenic ligand with those of the lanthanide to create unprecedented chiral SMMs (1) (Figure 1a), [36][37][38][39] efficient singlet oxygen sensitizers, [40] and strong MChD response in the NIR range of the electromagnetic spectrum. [41][42][43] Despite their pertinent chiroptical properties, chiral emissive Yb III complexes are still scarce. [18,19,[44][45][46][47][48][49] Herein, we describe the synthesis of the first homochiral monodimensional coordination polymer (1D-CP), namely M-and P-[H6(py) 2 Yb(hfac) 3 ] n 2 and its structural features.…”
Section: Introductionmentioning
confidence: 99%
“… [35] Recently, we have shown that 3‐(2‐pyridyl)‐4‐aza[6]‐helicene (H6bpy) bearing a 2,2′‐bipyridine coordinating unit can accommodate a lanthanide ion and combine the inherent properties of the helicenic ligand with those of the lanthanide to create unprecedented chiral SMMs ( 1 ) (Figure 1a ),[ 36 , 37 , 38 , 39 ] efficient singlet oxygen sensitizers, [40] and strong MChD response in the NIR range of the electromagnetic spectrum. [ 41 , 42 , 43 ] Despite their pertinent chiroptical properties, chiral emissive Yb III complexes are still scarce. [ 18 , 19 , 44 , 45 , 46 , 47 , 48 , 49 ] Herein, we describe the synthesis of the first homochiral monodimensional coordination polymer (1D‐CP), namely M ‐ and P ‐[H6(py) 2 Yb(hfac) 3 ] n 2 and its structural features.…”
Section: Introductionmentioning
confidence: 99%
“…A series of Eu­(III) complexes with chiral organic ligands, such as camphor, Pybox, naphthol, and helicene derivatives, have been reported. , The CPL properties of chiral Eu­(III) complexes are closely related to their coordination geometries and structural strain of ligands. Yuasa demonstrated that the cis – trans isomerization of the bidentate phosphine oxide ligand in a chiral Eu­(III) complex leads to CPL sign inversion .…”
Section: Introductionmentioning
confidence: 99%